A systematic review of modelling approaches in economic evaluations of health interventions for drug and alcohol problems. Issue 1 (December 2016) - Hoang, Van; Shanahan, Marian; Shukla, Nagesh; Perez, Pascal; Farrell, Michael; Ritter, Alison
Abstract Background The overarching goal of health policies is to maximize health and societal benefits. Economic evaluations can play a vital role in assessing whether or not such benefits occur. This paper reviews the application of modelling techniques in economic evaluations of drug and alcohol interventions with regard to (i) modelling paradigms themselves; (ii) perspectives of costs and benefits and (iii) time frame. Methods Papers that use modelling approaches for economic evaluations of drug and alcohol interventions were identified by carrying out searches of major databases. Results Thirty eight papers met the inclusion criteria. Overall, the cohort Markov models remain the most popular approach, followed by decision trees, Individual based model and System dynamics model (SD). Most of the papers adopted a long term time frame to reflect the long term costs and benefits of health interventions. However, it was fairly common among the reviewed papers to adopt a narrow perspective that only takes into account costs and benefits borne by the health care sector. Conclusions This review paper informs policy makers about the availability of modelling techniques that can be used to enhance the quality of economic evaluations for drug and alcohol treatment interventions.